Moral Positioning - Thomas Aström (Grounded Theory Review: An International Journal)
This article presents the main outlines of a theory of moral positioning, contributing to the analysis of moralizing as a social phenomenon. It is a formal theory in several of its aspects. The discovered patterns help to explain social interaction in conflicts and how ordinary people use these patterns in relation to others. Moral positioning is frequently occurring in social situations were imbalances and conflicts arise among individuals and groups. Moral positioning is here theorized concurrently with a supporting conceptualization of social positioning. The model here presented can be used to explain the positioning process and is possible to use in order to become aware of, and in a better way, manage a conflict.